E-Banking Service Quality: A Scale Development and Validation Attempt - Chandel, Ajay; Vij, Rohit (Indian Journal of Marketing, 2019)
Technology empowers banks to provide ease of use to customers at any time. This re-engineering in the banking system cemented the way banks' services reached to customers with ease and flexibility through multiple channels. The Internet has taken banks to homes and offices 365 days a year through electronic banking. Advent of electronic banking also called for pleasing customers with excellent service quality. Understanding electronic-banking service quality dimensions hence became extremely vital to electronic banking existence. Although there is no dearth of studies on service quality, relatively less research has been dedicated to exploring electronic banking service quality. This could be due to lack of a standardized scale measuring electronic banking service quality. This study, therefore, tried to identify and validate the dimensions determining electronic banking service quality and to measure the relative contribution of identified dimensions towards total electronic banking service quality in the context of India. Most often sited e-banking service quality dimensions mined from review of pertinent literature were used to generate 60 items. The items were content validated from 10 experts before administering to 400 respondents. The final questionnaire consisting of 30 items was distributed to 100 respondents each of two private and two public e-banking users (sample size of 400). Exploratory factor analysis yielded a six-factor structure. Confirmatory factor analysis (CFA) was used to verify the factor structure. Multiple regression was used to measure the relative contribution of identified dimensions towards total electronic banking service quality.